Attributing diseases to multiple pathways: a causal-pie modeling approach - Chen C; Lee WC (Clinical Epidemiology, 2018)
Christine Chen,1 Wen-Chung Lee1,2 1Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, Taiwan; 2Research Center for Genes, Environment and Human Health, College of Public Health, National Taiwan University, Taipei, Taiwan Abstract: Characterizing the relations between exposures and diseases is the central tenet of epidemiology. Researchers may want to evaluate exposure-disease causation by assessing whether the disease under concern is induced by the various exposures – the so-called “attribution”. In this paper, the authors propose a method to attribute diseases to multiple pathways based on the causal-pie model. The method can also be used to evaluate the potential impact of an intervention strategy and to allocate responsibility in tort-law liability issues. Keywords: epidemiological methods, attribution, disease pathways, causal-pie model